Membangun Perilaku Beragama yang Moderat melalui Internalisasi Nilai-nilai Pendidikan Kristiani pada Tradisi Budaya Lokal di Minahasa (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
Parenting in the family is an important factor in shaping adolescent character and adolescent spirituality. The family is a place where adolescents develop their character and spirituality, parenting provided by parents will have a significant impact on the character and spirituality of adolescents in loving God. The research method uses a quantitative approach to the type of Ex post facto research. The results showed (1) there was an influence of parenting style on adolescent spirituality, having a sig value of 0.01 with a Pearson Correlation value of -0.453. (2) there is an influence of adolescent character on adolescent spirituality, having a sig value of 0.048